Single-Cell RNA Sequencing Profiles Identify Important Pathophysiologic Factors in the Progression of Diabetic Nephropathy - Lu, Xi; Li, Li; Suo, Luolan; Huang, Ping; Wang, Hongjie; Han, Su; Cao, Mingming (Frontiers in Cell and Developmental Biology, 2022)
Objective: Single-cell RNA sequencing (scRNA-seq) analyses have provided a novel insight into cell-specific gene expression changes in diseases. Here, this study was conducted to identify cell types and pathophysiologic factors in diabetic nephropathy. Methods: Single-cell RNA sequencing data of 3 human diabetic kidney specimens and 3 controls were retrieved from the GSE131882 dataset. Following preprocessing and normalization, cell clustering was presented and cell types were identified. Marker genes of each cell type were identified by comparing other cell types. Ligand-receptor network analysis of immune cells was then conducted. Differentially expressed marker genes of immune cells were screened between diabetic nephropathy tissues and controls and their biological functions were analyzed. Diabetic nephropathy rat models were established and key marker genes were validated by RT-qPCR and western blot. Results: Here, 10 cell types were clustered, including tubular cells, endothelium, parietal epithelial cells, podocytes, collecting duct, mesangial cells, immune cells, distal convoluted tubule, the thick ascending limb, and proximal tubule in diabetic kidney specimens and controls. Among them, immune cells had the highest proportion in diabetic nephropathy. Immune cells had the close interactions with other cells by receptor-ligand interactions. Differentially expressed marker genes of immune cells EIF4B, RICTOR and PRKCB were significantly enriched in mTOR pathway, which were confirmed to be up-regulated in diabetic nephropathy. Conclusion: Our findings identified immune cells and their marker genes (EIF4B, RICTOR and PRKCB) as key pathophysiologic factors that might contribute to diabetic nephropathy progression.